The Issue of the Covid-19 Vaccine and the Impact on Health Services in Hospitals - Budi Sulistiyo Nugroho; Jenita Jenita; B.M.A.S. Anaconda Bangkara; Fadli Fadli; Sardjana Orba Manullang (Budapest International Research and Critics University, 2022)
This paper discusses the issue of the pandemic vaccine and its impact on health services in both public and private hospitals. The author believes that if a pandemic hits the world, the world leaders call for a united response to the pandemic issue by being very prepared and mobilizing all their energy and policies. For this reason, we want to understand how experts think about health services in hospitals and the issue of responding to the pandemic. Our data were obtained from various literary sources such as publications of scientific journals on public service health during the pandemic and various other reading sources that actively discussed the issue in question. The review effort involved a series of methods, including coding data interpretation of data in a detailed evaluation and concluding based on the validity of the data findings. Finally, after discussing the findings, we can conclude that the issue of pandemic vaccines impacts other health services in Indonesia. This is because government policies are very intense and focused on dealing with vaccines and other services.